Effect of integrated nutrient supply and management on yield of rice (Oryza sativa) and nitrogen and phosphorus recovery by it in acid lateritic solis - A. CHAKRABORTY; P.K. CHAKRABORN; P. BANIK; D.K. B (Indian Journal of Agronomy, 2001)
A field experiment was conducted during the rainy (kharit) seasons of 1996 and 1997 on rice (Olyza sativa L.) in acid lateritic soil of Sekhampore, Birbhum district, West Bengal. Highest green and dry matter of Sebania aculeata (SA) was obtained with the application of single superphosphate (SSP) 30 kg Plha as also the N and P content in dry matter. Grain and straw yields, N uptake and P recovery of rice were highest when S. aculeata was grown and incorporated followed by fertilizer application 39, 15 and 15 kg N,P, and Wha as basal dose r to rice. Uptake of P in rice and agronomic efficiency of N were maximum when S. aculeata was fertilized with single superphosphate 30 kg Plha and was incorporated prior to rice transplantation. The agronomic efficiency of P was higher with fertilizers applied 30, 15 and 15 kg N,P and Wha to rice after S. aculeata incorporation.